Protease-activated receptor (PAR)-2 is required for PAR-1 signalling in pulmonary fibrosis - Lin, Cong (J Cell Mol Med, 2015)
Idiopathic pulmonary fibrosis is the most devastating diffuse fibrosing lung disease of unknown aetiology. Compelling evidence suggests that both protease-activated receptor (PAR)-1 and PAR-2 participate in the development of pulmonary fibrosis. Previous studies have shown that bleomycin-induced lung fibrosis is diminished in both PAR-1 and PAR-2 deficient mice. We thus have been suggested that combined inactivation of PAR-1 and PAR-2 would be more effective in blocking pulmonary fibrosis. Human and murine fibroblasts were stimulated with PAR-1 and PAR-2 agonists in the absence or presence of specific PAR-1 or PAR-2 antagonists after which fibrotic markers like collagen and smooth muscle actin were analysed by Western blot. Pulmonary fibrosis was induced by intranasal instillation of bleomycin into wild-type and PAR-2 deficient mice with or without a specific PAR-1 antagonist (P1pal-12). Fibrosis was assessed by hydroxyproline quantification and (immuno)histochemical analysis. We show that specific PAR-1 and/or PAR-2 activating proteases induce fibroblast migration, differentiation and extracellular matrix production. Interestingly, however, combined activation of PAR-1 and PAR-2 did not show any additive effects on these pro-fibrotic responses. Strikingly, PAR-2 deficiency as well as pharmacological PAR-1 inhibition reduced bleomycin-induced pulmonary fibrosis to a similar extent. PAR-1 inhibition in PAR-2 deficient mice did not further diminish bleomycin-induced pulmonary fibrosis. Finally, we show that the PAR-1-dependent pro-fibrotic responses are inhibited by the PAR-2 specific antagonist. Targeting PAR-1 and PAR-2 simultaneously is not superior to targeting either receptor alone in bleomycin-induced pulmonary fibrosis. We postulate that the pro-fibrotic effects of PAR-1 require the presence of PAR-2.